Analisa Kemudahan Penggunaan Aplikasi AdaKami Dengan Menerapkan Metode Technology Acceptance Model (TAM) - Lubis, Julia Indriani; Siregar, Rizky Anggraini (CV. Graha Mitra Edukasi, 2024)
The problem in this research is that the AdaKami application often gets complaints from users, such as not being able to use or withdraw money even though the limit is high, difficulties in the application where errors often occur in the payment system, and users are subject to fines for late payments. To overcome these problems, research This method uses the Technology Acceptance Model (TAM) to analyze the ease of the AdaKami application. With this article, users can understand how to use the AdaKami application. We hope that the data collection carried out can help users use the features contained in the application. Overall, the PEAOU variable is included in the strongly agree category and it can be concluded that using the AdaKami application is relatively easy. With the results obtained by the PEOU variable of 68.4%.